Orthodontically induced inflammatory root resorption (OIRR). Part I: Biological risk factors - Sambevski, John; Darendeliler, M. Ali (Forum Ortodontyczne / Orthodontic Forum, 2019)
The majority of orthodontically treated patients exhibit some degree of root resorption with the reported prevalence from 0% to 100%. Orthodontic root resorption is multifactorial in nature and different biological factors were reported to play a role in its aetiology. Aim. The aim of the study was to discuss the role of biological factors in orthodontically induced inflammatory root resorption (OIIRR). Material and methods. The literature review of the etiology of OIIRR in relation to biological factors was performed based on the available medical database. Results. Genetic risk factors include individual susceptibility, gender, age and ethnicity. Medical history such as asthma and other allergies, endocrine abnormalities and use of different medications are also involved. The effect of systemic fluoride on root resorption was documented in animal experiments and epidemiological studies. The paper discusses the possible role of biological factors in aetiology of orthodontically induced root resorption. Conclusions. OIIRR etiology is multifactorial in nature and there is a complex relationship between individual biological or genetic susceptibility. (Sambevski J, Darendeliler MA. Orthodontically induced inflammatory root resorption (OIRR). Part I: Biological risk factors. Orthod Forum 2019; 15: 27-38).